Reflections on the concept of citizen participation: Aristotelian and neoaristotelian considerations (2018)
This article aims to analyze the concept of “citizen participation” from the classical perspective of Aristotle and the modern view of John Dewey taking into account the sociological dynamics of the contemporary era. For that, there will be a critical review of the historical-conceptual scaffolding proposed by Aristotle in the framework of the Athenian’s Constitution and the understanding of the Stagirite of notions such as city, political animal and justice as conceptual inputs connatural to the phenomenon of citizen participation. Afterwards, a general panorama of the contemporary political philosophy will be exposed, highlighting the influence of Aristotle in the current discussions about the concept of citizen participation, especially, the proposal of Dewey as a current alternative to explain the dynamics of citizen participation will be taken into account, as a normative option to improve the political conditions of current societies.